Dead Wings - Dahl, Michael; Piatti, Federico (Mankato, Minn. : Stone Arch Books, 2010)
When Taj wakes one morning to find that he is growing a pair of scaly wings, he turns to his trusted cousin Kumar, who bears the same dragon-shaped birthmark as his, for advice.
008-013.
RL: 1.7.
Guided Reading Level: L.
Keywords: Dragons -- Fiction; East Indian Americans -- Fiction